Intergenerational Educational Inequality and Its Transmission in China’s Elite Universities - Wei, Jianwen; Li, Shuanglong; Han, Yang; Fu, Wangqian (Frontiers in Psychology, 2022)
Abstract: China is experiencing high social inequality accompanying influential education reforms. The Independent Freshmen Admission (IFA) policy was one of the multiple strategies in higher education reforms in China against the social context of high social inequality and the expansion of higher education. By comparing students admitted through IFA with those admitted by the National College Entrance Examination (NCEE), we examined how family advantages contributed to higher education inequality in terms of educational opportunity, process, and results. Using data from an elite university in Beijing, we found that: 1) family advantages improved a student's likelihood of being admitted through IFA, exhibiting opportunity inequality. 2) No significant difference in academic grades existed between the students admitted through IFA and NCEE. In comprehensive quality, however, those recruited through IFA performed significantly better than those admitted through NCEE. 3) Family social capital not only increased the likelihood of students being admitted through IFA but also, through direct and indirect effects, increased their comprehensive quality performance in terms of receiving student association and social practice awards.